1995
DOI: 10.1029/94ja02420
|View full text |Cite
|
Sign up to set email alerts
|

An empirical determination of the polytropic index for the free‐streaming solar wind using Helios 1 data

Abstract: Observations of solar wind proton temperatures indicate that the solar wind is heated as it moves outward toward the orbit of Earth. This heating, which may be the result of electron heat conduction and perhaps MHD waves, has proven difficult to quantify and hence is often neglected in MHD models of the solar wind. An alternate approach to finding explicit heating terms for the MHD energy equation is to use a polytropic approximation. This paper discusses the properties of the polytropic approximation and its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
150
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(169 citation statements)
references
References 18 publications
18
150
1
Order By: Relevance
“…Démoulin & Dasso (2009) have shown theoretically that the main origin of MC expansion is the decrease of the total SW pressure with solar distance D. With a SW pressure decreasing as D −n P , they found that ζ ≈ n P /4 independently of the magnetic structure of the flux rope forming the MC. In the present work, we re-analyzed the total SW pressure variation with D, revising previous studies that also analyzed Helios data (Mariani & Neubauer 1990;Schwenn 2006;Totten et al 1995;Marsch et al 1989). We found n P = 2.91 ± 0.31, which implies n P /4 = 0.73 ± 0.08, in agreement with our estimation of ζ from the measured velocity in MCs.…”
Section: Summary and Discussion Of Main Resultsmentioning
confidence: 99%
“…Démoulin & Dasso (2009) have shown theoretically that the main origin of MC expansion is the decrease of the total SW pressure with solar distance D. With a SW pressure decreasing as D −n P , they found that ζ ≈ n P /4 independently of the magnetic structure of the flux rope forming the MC. In the present work, we re-analyzed the total SW pressure variation with D, revising previous studies that also analyzed Helios data (Mariani & Neubauer 1990;Schwenn 2006;Totten et al 1995;Marsch et al 1989). We found n P = 2.91 ± 0.31, which implies n P /4 = 0.73 ± 0.08, in agreement with our estimation of ζ from the measured velocity in MCs.…”
Section: Summary and Discussion Of Main Resultsmentioning
confidence: 99%
“…The small § dependence of with distance was unexpected. The temperature of the background solar wind in the inner heliosphere decreases as § 2 3 £ [Totten et al, 1995]. Since ICMEs expand with distance, the temperature in ICMEs should decrease faster than in the background solar wind due to adiabatic cooling; instead it decreases less quickly.…”
Section: Radial Evolution Of Icmesmentioning
confidence: 99%
“…Ulysses was launched in 1990 and orbits over the solar poles at 1.3 -5.4 AU (although most ICMEs detected are at low latitudes). Since the temperature decreases with distance, we normalized to 1 AU assuming a § 2 3 £ dependence [Totten et al, 1995; see also Steinitz and Eyni, 1981;Lopez and Freeman, 1995] before applying the temperature criteria. The…”
Section: Identification Of Icmesmentioning
confidence: 99%
“…The heliospheric model uses g = 5/3 to describe fully ionized solar wind plasma, which allows for obtaining accurate shock strengths. We have also performed heliospheric computations with an empirically based g = 1.5 which reflects nonideal processes in the solar wind [Totten et al, 1995]. The dynamical differences are small and g = 5/ 3 is used in this paper since the aim is to track the steepening of coronal pressure waves into interplanetary shocks.…”
Section: Numerical Modelsmentioning
confidence: 99%